Areas of Convergence and Divergence in Adolescent Social Isolation and Binge Drinking: A Review - Lodha, Jyoti; Brocato, Emily; Wolstenholme, Jennifer T. (Frontiers in Behavioral Neuroscience, 2022)
Abstract Adolescence is a critical developmental period characterized by enhanced social interactions, ongoing development of the frontal cortex and maturation of synaptic connections throughout the brain. Adolescents spend more time interacting with peers than any other age group and display heightened reward sensitivity, impulsivity and diminished inhibitory self-control, which contribute to increased risky behaviors, including the initiation and progression of alcohol use. Compared to adults, adolescents are less susceptible to the negative effects of ethanol, but are more susceptible to the negative effects of stress, particularly social stress. Juvenile exposure to social isolation or binge ethanol disrupts synaptic connections, dendritic spine morphology, and myelin remodeling in the frontal cortex. These structural effects may underlie the behavioral and cognitive deficits seen later in life, including social and memory deficits, increased anxiety-like behavior and risk for alcohol use disorders (AUD). Although the alcohol and social stress fields are actively investigating the mechanisms through which these effects occur, significant gaps in our understanding exist, particularly in the intersection of the two fields. This review will highlight the areas of convergence and divergence in the fields of adolescent social stress and ethanol exposure. We will focus on how ethanol exposure or social isolation stress can impact the development of the frontal cortex and lead to lasting behavioral changes in adulthood. We call attention to the need for more mechanistic studies and the inclusion of the evaluation of sex differences in these molecular, structural, and behavioral responses.